2001
DOI: 10.1177/002215540104900207
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Location and Expression Pattern of Autoimmune Regulator (Aire), the Mouse Orthologue for Human Gene Defective in Autoimmune Polyendocrinopathy Candidiasis Ectodermal Dystrophy (APECED)

Abstract: SUMMARY Autoimmune polyendocrinopathy candidiasis ectodermal dystrophy (APECED), also known as autoimmune polyglandular syndrome Type I (APS1), is an autosomal recessive autoimmune disease caused by mutations in a gene designated as AIRE (autoimmune regulator). Here we have studied the expression of Aire in transfected cell lines and in adult mouse tissues. Our results show that Aire has a dual subcellular location and that it is expressed in multiple immunologically relevant tissues such as the thymus, spleen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
3
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 34 publications
7
60
3
2
Order By: Relevance
“…Moreover, the PHD1 domain of AIRE has been suggested to have an E3 ubiquitin ligase activity in cell-free assays [19], findings in variance with a recent report [20]. Aire is highly expressed in a subset of the medullary thymic epithelial cells (mTEC) as well as in DC in the spleen and lymph nodes [21][22][23][24], indicating a potential role in immunological tolerance.To characterize the function of Aire, we previously engineered an Aire-deficient mouse targeting the most common APS I mutation [4]. Aire-deficient mice develop multiple organ-specific autoantibodies and lymphocytic infiltrates, thus mimicking some of the features of human APS I [4].…”
mentioning
confidence: 78%
“…Moreover, the PHD1 domain of AIRE has been suggested to have an E3 ubiquitin ligase activity in cell-free assays [19], findings in variance with a recent report [20]. Aire is highly expressed in a subset of the medullary thymic epithelial cells (mTEC) as well as in DC in the spleen and lymph nodes [21][22][23][24], indicating a potential role in immunological tolerance.To characterize the function of Aire, we previously engineered an Aire-deficient mouse targeting the most common APS I mutation [4]. Aire-deficient mice develop multiple organ-specific autoantibodies and lymphocytic infiltrates, thus mimicking some of the features of human APS I [4].…”
mentioning
confidence: 78%
“…The AIRE protein was not found in target organs of autoimmune destruction [157]. In adult mice, however, AIRE expression was found in bone marrow, kidney, testis, adrenal gland, liver and ovary [158,159]. The human and mouse AIRE promoters have conserved sites for several thymus-specific transcription factors consistent with its expression in rare cells of the thy-mus medulla, lymph nodes, and foetal liver.…”
Section: ªMonogenicº Diabetes Syndromesmentioning
confidence: 91%
“…The expression of Aire in the periphery is less clear. Some studies have reported Aire expressed in lymph nodes, in the peripheral monocyte/DC lineage, and a subset of lymph node stromal cells [8][9][10][11][12][13], while others suggest that it is rather unlikely that Aire is present in DC or lymph node epithelial cells [14].…”
Section: Cd8mentioning
confidence: 99%